2011
DOI: 10.1124/dmd.111.040675
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Species and Human Disposition of PF-04971729, a Selective Inhibitor of the Sodium-Dependent Glucose Cotransporter 2 and Clinical Candidate for the Treatment of Type 2 Diabetes Mellitus

Abstract: C]metformin by PF-04971729 also were very weak (IC 50 ‫؍‬ ϳ900 M). Single-species allometric scaling of rat pharmacokinetics of PF-04971729 was used to predict human clearance, distribution volume, and oral bioavailability. Human pharmacokinetic predictions were consistent with the potential for a low daily dose. First-in-human studies after oral administration indicated that the human pharmacokinetics/dose predictions for PF-04971729 were in the range that is likely to yield a favorable pharmacodynamic respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
128
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(130 citation statements)
references
References 39 publications
2
128
0
Order By: Relevance
“…An example is ertugluflozin (PF-04971729), a selective inhibitor of the sodium-dependent glucose cotransporter 2. Reaction phenotyping studies indicated that both P450 (CYP3A4/3A5) and non-P450 pathways (UGT1A9 and UGT2B7) are involved in the metabolism of this compound (Kalgutkar et al, 2011). However, quantitative assignment of each of these pathways was not feasible because of low in vitro turnover in hepatic microsomes and hepatocytes.…”
Section: Special Considerations: Low Turnover Extrahepatic Metabolismentioning
confidence: 99%
“…An example is ertugluflozin (PF-04971729), a selective inhibitor of the sodium-dependent glucose cotransporter 2. Reaction phenotyping studies indicated that both P450 (CYP3A4/3A5) and non-P450 pathways (UGT1A9 and UGT2B7) are involved in the metabolism of this compound (Kalgutkar et al, 2011). However, quantitative assignment of each of these pathways was not feasible because of low in vitro turnover in hepatic microsomes and hepatocytes.…”
Section: Special Considerations: Low Turnover Extrahepatic Metabolismentioning
confidence: 99%
“…In the ertugliflozin human mass balance study, ertugliflozin F a was estimated to be ≥50%,2 whereas in preclinical species, estimated F a was ∼75% and ∼100% in rats and dogs, respectively 1. In Caco‐2 cells, ertugliflozin permeability coefficient was 4.1 × 10 −6  cm/s in the apical (A) to basolateral (B) direction (BA/AB ratio of 2.1) 1. In light of these data, a clinical study was conducted to get a better understanding of permeability and obtain an estimate of the absolute bioavailability of ertugliflozin.…”
mentioning
confidence: 97%
“…Ertugliflozin, a highly selective and potent inhibitor of the sodium glucose cotransporter‐2,1, 2 has been approved in the United States for the treatment of type 2 diabetes mellitus at doses of 5 and 15 mg once daily. Recent phase III trials have demonstrated that ertugliflozin is associated with statistically significant reductions in hemoglobin A1c, fasting plasma glucose, and body weight when used as monotherapy (compared with placebo),3 and when added to sitagliptin4 or metformin plus sitagliptin 5.…”
mentioning
confidence: 99%
See 2 more Smart Citations